The availability, price, and characteristics of low sodium salt based on an online salt market survey in China: Implications for scaling up its use - Dejing Meng; Laura K. Cobb; Nicole Ide; Zeng Ge (The Journal of Clinical Hypertension, 2023)
Abstract Low sodium salt (LSS) is an effective way to reduce the primary source of sodium from home cooking. To investigate the availability, price and characteristics of LSS, price gap between LSS and regular salt, and the potential size of subsidy needed to equalize the price of LSS and regular salt. A market survey of salts was conducted using two major online shopping sites JD and Taobao from November to December 2022. Of 360 salts, 76 (21.1%) are LSS and 284 (78.9%) are regular salt. The average proportion of potassium chloride is low (16.8%), and half of the brands contain less than 15% and only 6.6% contains ≥25%. The mean price of LSS is slightly but not significantly higher than that of regular salts (1.82 versus 1.67 yuan/100 g, p = .07). In the lowest quartile by price, the cost of LSS is significantly higher than regular salts (difference 0.13, p = .0048). Further, when comparing the lowest price LSS to the lowest price regular since within the same brand, the mean price LSS is 2.11‐fold that of the regular salt (1.66 versus 0.79 yuan/100 g, p < .05). The price of iodized LSS is also significantly higher than that of iodized regular salt (1.86 verse 1.44 yuan/100 g, p = .044). An annual subsidy based on the difference in price in the first quartile would cost 4.75 yuan per capita. A variety of LSS are available in China's salt market.